2013
DOI: 10.1371/journal.pone.0056083
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Heat Shock Protein 90 for the Treatment of Malignant Pheochromocytoma

Abstract: Metastatic pheochromocytoma represents one of the major clinical challenges in the field of neuroendocrine oncology. Recent molecular characterization of pheochromocytoma suggests new treatment options with targeted therapies. In this study we investigated the 90 kDa heat shock protein (Hsp90) as a potential therapeutic target for advanced pheochromocytoma. Both the first generation, natural product Hsp90 inhibitor 17-allylamino-17-demethoxygeldanamycin (17-AAG, tanespimycin), and the second-generation synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…17-AAG (a derivative of the antibiotic geldanamycin) is a potent Hsp90 inhibitor that specifically binds to Hsp90's ATP-binding site and modulates its function (Whitesell et al, 1994; Prodromou et al, 1997; Pratt and Toft, 2003; Giubellino et al, 2013). The binding of these drugs to HSP90 facilitates the dissociation and activation of HSF1, which forms a complex with HSP90 in the resting cells (Figs.…”
Section: Hsp70 and Rgc Survivalmentioning
confidence: 99%
“…17-AAG (a derivative of the antibiotic geldanamycin) is a potent Hsp90 inhibitor that specifically binds to Hsp90's ATP-binding site and modulates its function (Whitesell et al, 1994; Prodromou et al, 1997; Pratt and Toft, 2003; Giubellino et al, 2013). The binding of these drugs to HSP90 facilitates the dissociation and activation of HSF1, which forms a complex with HSP90 in the resting cells (Figs.…”
Section: Hsp70 and Rgc Survivalmentioning
confidence: 99%
“…Thus, inhibitors of HSP90, such as geldanamycin and analogues like 17-allylaminogeldanamycin (17-AAG; tanespimycin), 17-dimethylaminoethylamino-17-demethoxygeldanamycin (17-DMAG; alespimicin), or other new analogues, are promising therapeutic agents (Isaacs, et al 2002; Northcott, et al 2012). Giubelino et al (Giubellino, et al 2013) demonstrated potent inhibition of proliferation and migration of PHEO cell lines and induced degradation of key Hsp90 clients by 17-AAG and ganetespib. They also showed the efficacy of 17-AAG and ganetespib in reducing metastatic burden and increasing survival in metastatic model of PHEO (Giubellino et al 2013).…”
Section: Future Treatment Options To Attack Metabolic Alterations In mentioning
confidence: 99%
“…Giubelino et al (Giubellino, et al 2013) demonstrated potent inhibition of proliferation and migration of PHEO cell lines and induced degradation of key Hsp90 clients by 17-AAG and ganetespib. They also showed the efficacy of 17-AAG and ganetespib in reducing metastatic burden and increasing survival in metastatic model of PHEO (Giubellino et al 2013). …”
Section: Future Treatment Options To Attack Metabolic Alterations In mentioning
confidence: 99%
“…The role of ERK-1/2 MAPK-signaling pathway and HSP90 in CXCL1 inhibition of ASMC migration ASMCs were treated for 1 h at 37˚C with either ERK-1/2 MAPK inhibitor PD184352 (2 mM; US Biological, Swampscott, MA) (34) or with different concentrations (1, 10, or 100 nM) of 17-N-allylamino-17-demethoxygeldanamycin (17-AAG), a low-toxicity profile pan inhibitor of HSP90 (35) (AG Scientific, San Diego, CA) prior to the addition of CXCL1 to the Boyden chamber. Controls were exposed to the same concentration of DMSO.…”
Section: Migration Assaymentioning
confidence: 99%